Andrology Male Reproductive Health and Dysfunction - Nieschlag, Eberhard; Behre, Hermann M.; Nieschlag, Susan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This is the 3rd, totally revised edition of a well-known textbook that continues to represent the gold standard in the literature on clinical andrology. It examines in depth all aspects of male reproductive health, encompassing the basic physiology of male reproductive function and a wide range of disorders. Each of the chapters is written by outstanding experts in the field. Among the topics covered are: Testicular function Sperm maturation and fertilization Diagnostic procedures Infertility Primary and secondary hypogonadism Late-onset hypogonadism Erectile dysfunction Genetic disorders Environmental influences Psychology and sexual medicine Testosterone therapy Assisted reproduction: TESE and ICSI Cryopreservation Male contraception Ethics in andrology This volume will serve as a textbook for the newcomer to andrology, while providing the experienced physician with a valuable reference work. It will appeal to all who are concerned with male reproductive health: Andrologists Urologists Endocrinologists Gynecologists Internists Pediatricians Basic scientists
Scope and Goals of Andrology -- Physiology of Testicular Function -- Physiology of Sperm Maturation and Fertilization -- Classification of Andrological Disorders -- Anamnesis and Physical Examination -- Imaging Diagnostics -- Endocrine Laboratory Diagnosis -- Cytogenetic and Molecular Genetic Investigations -- Semen Analysis -- Sperm Quality and Function Tests -- Testicular Biopsy and Histology -- Diseases of the Hypothalamus and the Pituitary Gland -- Disorders at the Testicular Level -- The Aging Male and Late-Onset Hypogonadism -- Diseases of the Seminal Ducts -- Disorders of Erection, Cohabitation, and Ejaculation -- Disorders of Androgen Target Organs -- Testicular Dysfunction in Systemic Diseases -- Environmental Influences on Male Reproductive Health -- Gynecology Relevant to Andrology -- Testosterone Therapy -- Empirical Therapies for Idiopathic Male Infertility -- Assisted Reproduction -- Cryopreservation of Human Spermatozoa -- Psychology of Fertility Disorders -- Sexual Medicine and Andrology -- Male Contribution to Contraception -- Vasectomy and Refertilization -- Approaches to Hormonal Male Contraception -- Pharmacological Approaches to Male Contraception -- Ethical Aspects of Reproductive Medicine.
Keywords: Medicine; Dermatology; Gynecology; Endocrinology; Reproductive Medicine; Urology; Medicine & Public Health; Urology/Andrology.; Reproductive Medicine; Endocrinology; Gynecology; Dermatology